Phytofabricated Br-AgNP synthesis using Brassica oleracea var. italica and their anti-carcinogenic applications. (2023) - Puranik, Shubhangi; Patel, Imran
Abstract: Nanobiotechnology involves extraction of reducing agents from biological sources and their application for synthesis of nanoparticles. This study is based on identification and purification of natural reducing agents in medicinal plants like Brassica oleracea var. italica to analyse their anti-cancerous potential against HeLa and THP-1. Biogenic reduction of silver nanoparticles was performed using these plant extracts by single step bottom up approaches. Colorless to red coloured solution and a peak at 417 nm in UV–vis spectroscopy confirmed the synthesis of AgNPs. Scanning Electron Microscopy confirmed the spherical nature of AgNPs whereas XRD confirmed the crystalline nature. PSA, SEM and Zeta potential analyzer confirmed the AgNPs with range of size between 14.53 and 38.15 nm with higher stability. AgNPs were treated with HeLa and THP-1 cell line. The % inhibition from AgNPs on HeLa cell line was found to be highest at 80 μl concentration (26.3 %) and lowest at 10 μl concentration (19.49 %) whereas on THP-1 cell line was found to be highest at 80 μl concentration (22.96 %) and lowest at 10 μl concentration (2.26 %).